Introduction. Local Peacebuilding through a Gender Lens - Elisabeth Prügl; Rahel Kunz; Mimidoo Achakpa; Henri Myrttinen; Joy Onyesoh; Arifah Rahmawati; Christelle Rigual; Wening Udasmoro (Revue Internationale de Politique de Développement)
Around the world, people and communities transform violent conflicts and build peace in various ways. Such local practices have been widely documented in various disciplines but have rarely been studied in the field of peace and conflict studies. These practices highlight the ways in which peacebuilding involves various axes of difference that intersect with one another, including gender, age, class, ethnicity, religion and political ideologies. Adopting a feminist approach, we analyse such intersecting differences to develop a better understanding of the multiple and complex ways in which gender is present in peacebuilding practices, and of how it both enables and obstructs transformative goals. We address the question: How does gender inform peacebuilding initiatives in intersection with other social dynamics and identity categories, and to what effect? Identifying a number of gender logics, we show how intersectionally gendered dynamics shape and are shaped by peacebuilding initiatives. We analyse how gender becomes productive either by being deployed strategically or by asserting itself inadvertently, for example through gender stereotypes, gendered divisions of labour, or identity constructions. We build on the outcomes of a six-year collaborative research project involving scholars from Indonesia, Nigeria and Switzerland that centred on investigating peacebuilding initiatives at local, meso- and macro-levels in Indonesia and Nigeria.